Portugal : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper examines the education system and public investment in Portugal. Both areas are generally considered as critical for Portugal's prospects for sustaining or accelerating the drive toward real income convergence. Moreover, both areas absorb a substantial share of public resources and thus have important implications for fiscal balances, which are, under European Monetary Union, constrained by the Stability and Growth Pact. The paper assesses the performance of the Portuguese education system and delineates a possible agenda for reform. It also attempts to shed light on the role of public investment in Portugal.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet